Pengaruh Influencer, Flash sale Dan Harbolnas Terhadap Impulsive Buying - Lilis Handriani; Judi Suharsono; Khusnik Hudzafidah (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The research was conducted to determine the Infuence of Influencer, flash sale and harbolnas on Impulsive buying. The type of research used quantitave. The population in this study were active students of the 2020 Faculty of Economics and Business, Panca Marga University, Probolinggo.The sample is used by incidental sampling which amounts 40 responden with determinantion of each variable multiplied by 10. The data needed in the form of primer in the form questionnares. The data was analyzed using statistics in the form validity, reliability, classic assumption test, multiple regression analysis, and hypothesis testing and in its processing using Statistical Packages for Social Science (SPSS). Data analysis methods include validity test, reliability test, multicollinearity test, autocorrelation test, heteroscedasticity test, normality test, multiple liear regression analysis, det erminant analysis (R2), t test (partial). Based on the results of the partial test hypothesis test (t test) that has been carried out with a significance level of 5% it can be concluded that 1) Influencer with a tcount value of 4.913 is greater than ttable 2.028. 2) flash sale with a tcount value are 2.130 greater than ttable 2.028. 3) harbolnas with tcount value is 0.935 smaller than ttable 2.028.